Numerical modelling of micro-seismic and infrasound noise radiated by a wind turbine. Issue 99 (August 2017) - Gortsas, Theodore V.; Triantafyllidis, Theodoros; Chrisopoulos, Stylianos; Polyzos, Demosthenes
Abstract: Infrasound, low frequency noise and soil vibrations produced by large wind turbines might disturb the comfort of nearby structures and residents. In addition repowering close to urban areas produces some fears to the nearby residents that the level of disturbance may increase. Due to wind loading, the foundation of a wind turbine interacts with the soil and creates micro-seismic surface waves that propagate for long distances and they are able to influence adversely sensitive measurements conducted by laboratories located far from the excitation point. A numerical study on the creation and propagation of those waves to the surrounding area is the subject of the present work. Besides, the contribution of those waves to airborne sound generated by the soil-air interaction is also investigated. All numerical simulations are performed with the aid of the Boundary Element Method (BEM), which is ideal for solving such problems since it takes automatically into account the radiation conditions of the waves and thus only the soil-foundation interface and the free surface of the surrounding soil are needed to be discretized. Foundation and soil are considered as linearly elastic materials with interfacial bonding. The frequency domain Helmholtz equation is employed for the simulation of acoustic waves. Numerical results dealing with the airborne and soil borne noise propagation and attenuation are presented and disturbances that might be caused to nearby and far-field structures are discussed. Highlights: Most of the seismic waves generated by the vibrations of a WT spread as Rayleigh waves. The generated micro-seismic waves affect the measurements of seismological centers located even 15 km far from a WT farm. Bigger disturbances are produced at the frequency range of 5–10 Hz and The operation of a WT under strong winds generates micro-seismic waves that would cause annoyance for the neighbors. Since airborne and soil borne noise produced by a WT propagate as cylindrical and Rayleigh waves, respectively, 2D simulations of that fluid-structure interaction problem have been performed for a specific geometry and a structure located 500 m far from the WT. The most important conclusions here are (i) the micro-seismicity creates higher levels of noise inside a house than that of the airborne noise radiated by a WT and (ii) bedrock being in low depths underneath the soil has an additional contribution to the generated acoustic noise by the induced micro-seismicity.